The Design-Debrief: Using Storytelling to Connect Preservice Teacher Reflection With Design-Thinking (LEARNing Landscapes, 2018)
As a teacher educator, I prepare preservice students for regular reflection about teaching and learning by incorporating design-thinking and storytelling. In order to facilitate more interactive reflection on students’ early teaching experiences, I developed the design-debrief—a classroom activity that asked students to story their teaching experience with first-graders using the design-thinking process. I make connections to how design-thinking and storytelling enabled a more complex and systematic way to approach teacher reflection.
Keywords: storytelling and design-thinking teacher reflection; design-thinking; storytelling